CONSIDERATION OF THE IMPACT OF HIGH HARMONICS WHEN SELECTING THE CONDUCTOR CROSS-SECTIONS OF LINES OF OUTDOOR LIGHTING - V. B. Kozlovskaya; V. N. Kalechyts (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The operating mode of the lighting line depends on the correct choice of conductor cross section. The magnitude of the cross section has an influence on the provision of the required voltage levels on the light sources. The choice of the conductor cross section has been fulfilled based on calculations of the operating mode of the standard line of outdoor lighting specified in the article. Luminaries with high pressure sodium lamps connected through electromagnetic ballasts were used as sources of light. When choosing the conductor cross section of light lines a number of simplifications are commonly used. Attention is paid to the choice of sections without such assumptions: the inductive resistance of conductors is taken into account; the power of the luminaire depends on the voltage level in it. Luminaries with high pressure sodium lamps are the sources of high harmonics. Three variants of calculation are demonstrated depending on the accounting (or non-accounting) of high odd harmonics. The methods of calculating the mode of the lighting line are also presented in the article. The calculation is performed with the aid of Mathcad software. Operating parameters for each phase of the line (i.e. voltage in the items of the scheme, power, currents, power, and voltage losses in all the sections) were determined. The diagrams of the voltage distribution at items of the lighting line for three variants of calculation are plotted for various sections of aluminum conductors. On this basis the choice of the optimum magnitude of the conductor cross section of the lighting line was made. The obtained results of different calculation variants are compared. The comparison of the results obtained with the use of various methods of calculation was made. The impact of high harmonics on the operating mode of the line under consideration has been analyzed. The presence of high harmonics causes an increase of voltage losses, the distortion of sinusoidal voltage. The current of neutral conductor is comparable with the current of phase conductors, besides, the harmonics multiple of 3 are of great importance as they influence on the magnitude of the current.